2021
DOI: 10.1001/jamaophthalmol.2021.2795
|View full text |Cite
|
Sign up to set email alerts
|

Presumed SARS-CoV-2 Viral Particles in the Human Retina of Patients With COVID-19

Abstract: ARS-CoV-2 is an enveloped positive-sense RNA coronavirus belonging to the Coronaviridae family, and its cellular entry depends mainly on the binding of S protein 1,2 to angiotensin-converting enzyme 2, a specific cellular receptor located at the surface of the host cells. 3,4 The SARS-CoV-2 viral particles' presence in the retina of deceased patients with COVID-19 has been suggested through the real-time polymerase chain reaction (PCR) and immunological methods to detect its main proteins. The eye is affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 16 publications
1
40
0
3
Order By: Relevance
“…Histopathologic specimens from the retinas of deceased patients with COVID-19 have found presumed SARS-CoV-2 viral particles in the ganglion cell layer, inner plexiform, inner nuclear, outer plexiform, outer nuclear layer, retinal pigment epithelium, and choroid. 41 A literature review found that COVID-19 was associated with an 8.86-fold risk of retinal vascular microvasculopathy, including retinal hemorrhages, cotton wool spots, infarcts at the internal plexus, and thinner ganglion cell layer and inner nuclear layer. 42 More severe systemic disease was associated with lower vascular density on OCT angiography (OCTA).…”
Section: Ocular Manifestations In Adults and Childrenmentioning
confidence: 99%
“…Histopathologic specimens from the retinas of deceased patients with COVID-19 have found presumed SARS-CoV-2 viral particles in the ganglion cell layer, inner plexiform, inner nuclear, outer plexiform, outer nuclear layer, retinal pigment epithelium, and choroid. 41 A literature review found that COVID-19 was associated with an 8.86-fold risk of retinal vascular microvasculopathy, including retinal hemorrhages, cotton wool spots, infarcts at the internal plexus, and thinner ganglion cell layer and inner nuclear layer. 42 More severe systemic disease was associated with lower vascular density on OCT angiography (OCTA).…”
Section: Ocular Manifestations In Adults and Childrenmentioning
confidence: 99%
“…Numerous case reports and studies on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection have revealed the retinal manifestations of the disease, which include arterial and venous thrombosis associated with macular edema (ME), haemorrhages, microvascular alterations and acute macular neuroretinopathy [ 1 – 5 ]. In addition, SARS-CoV-2 viral particles were reported to be present in human retina specimens from deceased patients infected with the disease [ 6 , 7 ]. However, it is unclear whether the reported findings are incidental, the result of systemic action of the virus or from direct retinal toxicity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“… 46 Furthermore, Araujo-Silva et al illustrated the findings of presumed viral particles within the retina of three deceased COVID-19 patients. 47 …”
Section: Discussionmentioning
confidence: 99%